Characterization and utilization of calabash (Crescentia cujete) fruit in wine making. - Del Rosario, Kwin Cybil Protacio
Calabash (Crescentia cujete), a rare type of fruit with limited uses in the Philippines, was characterized and its potential for wine production was evaluated. The survey revealed that this fruit is used mainly as juice for medicinal purposes and its shell as ornaments. The calabash which weighs 5-6 kilos has approximately 60.27% pulp, pH of 4.66 and total soluble solids (TSS) of 8.3°Brix. The moisture content, fiber, ash, protein, fat, and carbohydrates were 90.67%, 1.62%, 0.49%, 1.42%, 0.21%, 5.56%, respectively. The high moisture content of the fruit suggested that it was suited for wine making. Two formulations of calabash wine were compared, F1 (pulp:water ratio of 1:2, TSS of 24°Brix, with 0.05% yeast w/v) and F2 (pulp:water ratio of 1:1, TSS of 24°Brix, with 0.05% yeast w/v). The 15-day fermentation at room temperature (26-30°C) yielded wines with alcohol content of 12.21% - 12.23% which conformed to standard values. During fermentation, there was a significant decrease in the TSS and significant increase in the alcohol content (two-way ANOVA at α = 0.05). A strong negative linear relationship existed between TSS and alcohol content with r = -0.8926 and r = -0.9410 for F1 and F2, respectively. Wines from the two formulations significantly differed in pH, TSS, and titrable acidity (TA) during fermentation (two-way ANOVA at α = 0.05). A strong negative linear relationship existed between TSS and alcohol content with r = -0.8926 and r = -0.8926 and r = -0.9410 for F1 and F2, respectively. Wines from the two formulations significantly differed in pH, TSS, and titrable acidity (TA) during fermentation (two-way ANOVA at α = 0.05). The alcohol content between two formulations showed no significant different difference (two-way ANOVA at α = 0.05). The pH conformed to the standard values of 3.6-4.5 for most common wines. The titrable acidity, however, was below the range of the standard TA for most tropical wines. Between the two formulations, wine from F1 was significantly preferred than wine from F2 (Paired-preference Test at α = 0.05). Wine produced from F1 was raw umber in color, slightly sweet, with slightly detectable calabash-like aroma, and a very strong alcoholic aroma. Forty out of 50 respondents rated the product from like moderately to like very much. Ten respondents rated the product as like slightly. This indicates that the calabash which has a potential for commercialization.